Analysis of the Optimal Location for the Development of Senior High School Facilities in Response to the Zoning System in Siak Hulu District Using Geographic Information Systems - Pratama, Crismon Alfajri Agus Pratama; Nasution, Kenny (Tinta Emas Publisher, 2024)
The presence of the zoning system in the education system in Indonesia as a provision for determining the location of new students affects the mobility patterns of school-age children in Siak Hulu District. The level of education is one of the indicators in measuring the Human Development Index in an area. However, the level of education must be balanced with the number of educational facilities that accommodate efforts to improve human quality. This sub-district, which has 12 villages with a total area of 98,707 hectares, has only 3 high school facilities, while when reviewed in SNI No. 3/1733/2004 the service coverage of high schools is only 3000 square meters with a population of 4,800 people. In addition, the zoning system that has been regulated does not include 3 villages in the zoning of Senior High School facilities in Siak Hulu District. This research seeks to provide recommendations for unserved areas linked to the zoning regulations in Siak Hulu Sub-district. The method used in this analysis is spatial data analysis with the weighting method and compared through weighted overlay. The results of the analysis show that there are three villages that are optimal locations for the construction of new high schools, namely Kepau Jaya Village, Tanjung Balam Village and Pangkalan Serik Village.